كه‌لێنی خۆراكی برنج له‌ هه‌رێمی كوردستان له‌ نێوان ساڵی (2010-2021) - تالیب, پ. د. جه‌زا تۆفیق; مسته‌فا, م.ی. ڕۆسته‌م جه‌بار (Sulaimani Journal for Humanities, 2023)
Rice is a sort of food in which the demand for this kind of food will rise along with the increase of population in Kurdistan Region. It has been regarded as the second largest food after wheat in this area. According to the standards of the World Food and Agriculture Organization of the United Nations 36 kg of rice is needed in the Kurdistan Region for each person. More than 90% of rice is imported from India, Pakistan, Philippines, Thailand, Argentina and other countries to Kurdistan Region to fill the food gap. The Kurdistan Region has a suitable environment for developing and increasing and producing rice due to its natural environment such as water, air, soil, human factors such as labor and technology such as seeding and harvesting machines and chemical fertilizers.There is a great demand for local rice in the Kurdistan Region and abroad. In the future, rice can be marketed inside and outside the Kurdistan Region, despite the monthly food rations provided by the Iraqi Ministry of Commerce R individual (3) kg per month However, the quality of the rice distributed is not very good, so that it cannot fill the food gap of the entire population. The Kurdistan Region needs to Increase the area of rice production in the market and the price of rice in the regional markets Kurdistan and meet the food needs of some of the poor and middle class.
Keywords: (Rice food gap; demand; Kurdistan Region